Kafka : the decisive years - Stach, Reiner (Princeton University Press, 2013)
The acclaimed central volume of the definitive biography of Franz Kafka. Reiner Stach spent more than a decade working with over four thousand pages of journals, letters, and literary fragments, many never before available, to re-create the atmosphere in which Kafka lived and worked from 1910 to 1915, the most important and best-documented years of his life. This period, which would prove crucial to Kafka's writing and set the course for the rest of his life, saw him working with astonishing intensity on his most seminal writings-- The Trial, The Metamorphosis, The Man Who Disappeared (Amerika), and The Judgment. These are also the years of Kafka's fascination with Zionism; of his tumultuous engagement to Felice Bauer; and of the outbreak of World War I.